Pengaruh Tingkat Pertumbuhan Aset, Struktur Aktiva, Corporate Social Responsibility dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan pada Sektor Pertambangan di BEI Periode 2018-2020 - Komang Ayu Junika Triana; Gusti Ketut Rencana Sari Dewi (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of asset growth rate, asset structure, corporate social responsibility and company size on the company's financial performance in the mining sector on the IDX for the 2018-2020 period. The population in this study were 46 mining sector companies listed on the Indonesia Stock Exchange and the number of samples used were 23 mining sector companies listed on the Indonesia Stock Exchange. The quantitative data in this study is the annual report data of mining sector companies listed on the IDX in 2018-2020. The data analysis method used in this study is a multiple linear analysis method with the help of SPSS version 24. The results show that the growth rate has a positive and significant effect on company performance, asset structure has a positive and significant effect on company performance, Corporate social responsibility has a positive and significant impactcompany performance, and company size have a positive and significant effect on company performance.